2018
DOI: 10.1371/journal.pone.0199121
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping in bread wheat subjected to independent and combined high temperature and drought stress

Abstract: Most investigations to date aiming to identify the genetic basis of the stress response of wheat (Triticum aestivum L.) have focused on the response to single stress agents such as high temperature or drought, even though in the natural situation, these stresses tend often to occur together. Here, a panel of 108 spring type bread wheat cultivars was phenotyped for 15 yield and yield related traits for two years (2014/15 and 2015/16) under non-stressed conditions, under high temperature stress, under drought an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
79
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 69 publications
(75 reference statements)
7
79
1
1
Order By: Relevance
“…Grain number was mostly increased by the same allele as grain weight in both GWAS and NILs, indicating an important factor under post-anthesis drought and heat stress. Grain number is known to be affected by pre-anthesis stress (Fabian et al, 2019) but has also been found to be decreased by postanthesis stress (Prasad et al, 2011;Qaseem et al, 2018). Grain number, in our experiments, accounted for only well-filled grains Alleles for Drought and Heat Tolerance in Wheat (i.e., grains of size > 2.0 mm).…”
Section: Important Drought and Heat Tolerance Traitsmentioning
confidence: 40%
See 4 more Smart Citations
“…Grain number was mostly increased by the same allele as grain weight in both GWAS and NILs, indicating an important factor under post-anthesis drought and heat stress. Grain number is known to be affected by pre-anthesis stress (Fabian et al, 2019) but has also been found to be decreased by postanthesis stress (Prasad et al, 2011;Qaseem et al, 2018). Grain number, in our experiments, accounted for only well-filled grains Alleles for Drought and Heat Tolerance in Wheat (i.e., grains of size > 2.0 mm).…”
Section: Important Drought and Heat Tolerance Traitsmentioning
confidence: 40%
“…Ten of the 16 identified QTL for grain weight corresponded to QTL identified by Sun et al (2017), of which two, located on chromosomes 1A and 7A, regulated grain weight per spike. Six other QTL associated with grain weight were detected under well-watered, rainfed, or heat conditions Valluru et al, 2017;Wang et al, 2017;Qaseem et al, 2018) and coincided with the QTL for grain weight under DH and the heat response under drought on chromosome 3B, 5B, and the long arm of chromosome 6B (QGWp.adh-3B.1, QGWp.adh-3B.2, QGWp.adh-5B, QGWt.ara-6B.7, QGWp.ara-6B.3). The QTL on the long arm of chromosome 6B also co-located with QTL for harvest index under combined drought and heat stress (Garcia et al, 2019) as well as single grain weight and leaf chlorophyll content under heat (Shirdelmoghanloo et al, 2016).…”
Section: Novel Qtl For Drought and Heat Tolerancementioning
confidence: 91%
See 3 more Smart Citations